THEORETICAL AND METHODOLOGICAL BASIS OF THE ORGANIZATION OF INDEPENDENT WORK OF BACHELORS (DIRECTION "STATE AND MUNICIPAL MANAGEMENT") - Maksim N. Gordeev (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article analyzes the theoretical and methodological foundations of the organization of independent work of bachelors. The ability of self-education is becoming one of the cornerstones of competencies that form the basis of education and training policy in the European Union. Competence is seen as a mixed model in the bachelor. Considerable attention is paid to defining the essence of the concept of "self-study". In determining the theoretical and methodological nature of independent work of students, the key markers of independent work were identified, however, the question of an exhaustive list of markers remains controversial. This problem is poorly understood and requires further research. Using the analysis of the theoretical basis of research, the contradictions arising from the organization of independent work were formulated, and the directions of the design of the educational process were singled out. The paper emphasizes the distinction between "self" and "self-study". The role of self-competence in the formation and the formation of a bachelor is indicated. The idea that self-educational competence is an integrative indicator of the degree of formation of independent work on the mastery of competencies of narrow section of a bachelor is grounded, these competences in training bachelors in the direction "State and municipal management" (hereinafter "SMM") being management competences. Implementing the provisions of the competency approach, the interactive, active, and information and communication forms and technologies should be widely applied in the organization of the independent work of bachelors 'SMM' . Such a view would be of interest to specialists in the field of management training. In conclusion, the idea that the organization of independent work will be more successful in an integrated approach in the formation of core competencies, as well as the implementation of the competence-based approach is stated.